1985
DOI: 10.1079/bjn19850130
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and metabolism of glucose by the mesenteric-drained viscera of sheep fed on dried-grass or ground, maize-based diets

Abstract: 1. Sheep fitted with re-entrant canulas in the proximal duodenum and terminal ileum were used to determine the amount of a-glucoside entering, and apparently disappearing from, the small intestine when either dried-grass or ground maize-based diets were fed. The fate of any a-glucoside entering the small intestine was studied by comparing the net disappearance of such a-glucoside from the small intestine with the absorption of glucose into the mesenteric venous blood.2. Glucose absorption from the small intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
5
36
0
Order By: Relevance
“…The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes. High variability (.25%) in blood flow across the MDV has been observed previously (MacRae et al, 1997b;Yu et al, 2000), and might be attributed to either incomplete mixing of the dye in those blood vessels or movement of the catheter due to peristaltic intestinal contractions (MacRae et al, 1997b).…”
Section: Discussionsupporting
confidence: 82%
“…The net flux of AA across the MDV in the current study (1 to 5 g/day) is similar to the 4 to 6 g/day reported by MacRae et al (1997b) at similar intakes, but the similar net fluxes of AA across the MDV between control and parasitised lambs contrast with the observations for leucine by Yu et al (2000). While mesenteric plasma flows are within the ranges in the literature for sheep at a similar age and DM intake (700 to 1000 ml/min; Janes et al, 1985;MacRae et al, 1997b;Yu et al, 2000;Bermingham et al, 2007b), they are highly variable (CV of 28% to 40% in the control and parasitised lambs, respectively), and this variability may have masked any effects of infection on MDV AA fluxes. High variability (.25%) in blood flow across the MDV has been observed previously (MacRae et al, 1997b;Yu et al, 2000), and might be attributed to either incomplete mixing of the dye in those blood vessels or movement of the catheter due to peristaltic intestinal contractions (MacRae et al, 1997b).…”
Section: Discussionsupporting
confidence: 82%
“…In these cases, the endogenous hepatic glucose production was significantly reduced but not on a 1:1 basis, such that the rise in glucose absorption was accompanied by a rise in whole body glucose turnover. Similarly, exogenous glucose supply, either via intraduodenal or intrajugular infusions, increases glucose turnover in sheep [11,23] despite some reduction in endogenous glucose synthesis (noted by 59 only). The degree of inhibition of endogenous glucose synthesis is dose dependent with intrajugular infusions of glucose up to 0.5 mmol·min -1 [26].…”
Section: Glucose Precursors and Glucose Turnovermentioning
confidence: 99%
“…The previous survey of the literature specifically indicated that the inclusion of maize in the diet improves glucose turnover. With maize based diets, rich in bypass starch, absorbed glucose may contribute to glucose turnover to a variable but sometimes to a considerable extent (up to 60% [23,27,31]). In beef steers fed dry-rolled sorghum, it was evaluated that glucose absorption from starch intestinal digestion could account on average for a third of the glucose metabolism [6].…”
Section: Glucose Precursors and Glucose Turnovermentioning
confidence: 99%
“…The inconsistency of effects of supplemental propionate on blood glucose metabolism may be involved in the dose, duration or method of propionate supplementation, the stage of animals, or feeding managements. Although basal blood GTR was within the ranges of blood GTR as determined by the isotope dilution methods using stable and radio isotopes, blood GTR for the Prop diet seemed to be near the upper margin [12,18,28,29]. Because blood GTR is influenced by the type of diet, energy intake and physiological status [28][29][30], these factors may be related.…”
Section: Discussionmentioning
confidence: 81%
“…Although basal blood GTR was within the ranges of blood GTR as determined by the isotope dilution methods using stable and radio isotopes, blood GTR for the Prop diet seemed to be near the upper margin [12,18,28,29]. Because blood GTR is influenced by the type of diet, energy intake and physiological status [28][29][30], these factors may be related. OrtiguesMarty et al [29] reviewed the relationship between glucose turnover rate and ME intake in growing ovines, growing bovines and adult ovines, and suggested that growth stage on glucose turnover rate is probably as important as the effect of animal species.…”
Section: Discussionmentioning
confidence: 81%